ANALYSIS OF SATISFACTION IMPACT TOWARD REPLACEMENT OF GOODS INVENTORY METHOD WITH ABC METHOD IN IMPROVING PRODUCT QUALITY (CASE STUDY. UD. RIZKY ASSILA ULFA) - Yahya Tanjung; Apriliyanti Apriliyanti (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2020)
Methods are necessary in the process of listing the goods. If an enterprise does not implement a method in the proper process of listing the goods, there will be an error in determining the amount of inventory at the end of the period. The ABC method is one of the cost analysis counting approaches that helps management to analyse the basis of cost calculations in a more rewarding and UD company. Rizky Assila Ulfa is one of the companies that need to implement the ABC method because of UD. Rizki Assila Ulfa still implementing the traditional methods of inventory, so that often make mistakes in determining the price of profit obtained does not correspond to the production costs incurred, resulting in distortion or error in determining the cost of the production of goods. The analysis method is used in the form of multiple linear regression analysis techniques. The results of a research analysis conducted with an alpha of 5% showed that simultaneously between variable responsibilities, employee performance and product quality affects the use of ABC methods. However, a partial variable of responsibility and employee performance affects positively and significantly towards the use of the ABC method. While product quality variables have a positive effect but not significant so have no influence on the ABC method.